La vulnérabilité face aux changements climatiques - Gagnon-Bouchard, Laurie (Spirale, 2022)
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; cours; environnement; fem3600; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; écoféminisme

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

Écoresponsabilité : la nouvelle « charge morale » des femmes - Lemelin, Silvie (2020)
Apparu dans les années 1980, le concept de charge mentale a été popularisé et brillamment illustré par Emma dans sa désormais célèbre bande dessinée Fallait demander [1]. La charge mentale, c’est la charge cognitive invisible que représentent la planification, l’organisation et la gestion de tout ce qui se situe dans la sphère domestique (tâches ménagères, rendez-vous, achats, soins aux enfants, etc.) et qui, chez les couples hétérosexuels[2], échoit généralement aux femmes en plus de leur activité professionnelle. Car les hommes, consciemment ou pas, désignent souvent leur compagne comme la responsable en titre de la logistique familiale. Et ce travail invisible prend énormément de temps et d’énergie psychique ; il génère davantage de stress que l’accomplissement des tâches domestiques comme telles, la charge mentale accompagnant les femmes au boulot et dans toutes leurs activités.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; amériques; approches et analyses; care; charge mentale; environnement; hétérosexisme; inégalités; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; travail invisible

Surviving the grind: how young black women negotiate physical and emotional labor in urban space - McCurn, Alexis S. (Sociological Spectrum, 2020)
This study draws on nearly 2 years of field research in Central East Oakland, CA, to provide an ethnographic account of the daily experiences of poor, young, black women in urban space. Few scholars have explored the collective experiences of young women living in the inner-city and the innovative strategies they develop to navigate daily life in this setting. The accounts from young women in this study reveal the different types of formal and informal labor black women do to ensure survival in the inner-city and how they describe this daily work as the “grind.” The intersection of formal and informal labor that makes up the grind is reflected in three dimensions: the half-time hustle, underground entrepreneurship, and informal support networks. Like men in the neighborhood women must contend with underemployment, poverty and race and class isolation. I explain how black women are impacted in very specific ways by these key structural shifts and harsh structural conditions and must in turn manage constraining and contradictory gendered expectations while negotiating the grind. © 2020, © 2020 Taylor & Francis Group, LLC.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; capitalisme; environnement; intersectionnalité; milieu urbain; projet charge mentale; périodes historiques; racisme; régions géographiques; sexisme; stratégie de survie; systèmes d'oppressions; thématiques; travail; états-unis

Dénoncer les féminicides des femmes autochtones aux États-Unis et au Canada La bande dessinée Deer Woman d’Elizabeth LaPensée, une super-héroïne autochtone éco-féministe ? - Bonadè, Sophie; Hamus-Vallée, Réjane; Journée-Duez, Aurélie (Genre en séries, 2019)
À travers l’analyse de la bande dessinée Deer Woman créée en 2015 par Elizabeth LaPensée (Anishinaabe, Canada), notre article a pour objectif principal d’interroger la notion de « super-héroïne » à l’aune de représentations autochtones engagées. Il s’agit de voir en quoi cette revitalisation du mythe traditionnel de la Femme Cerf (Deer Woman) interroge l’identité en termes de sexe et de genre, la culture et la place des femmes autochtones, en prenant une position radicale face au problème sociétal des féminicides en Amérique du Nord. Nous postulons que la figure de Deer Woman peut aussi être vue aujourd’hui comme une allégorie mettant en garde contre la domination masculine sur les femmes et sur toutes autres formes de vie. Tout d’abord, nous étudierons les caractéristiques formelles de Deer Woman et les mythes fondateurs autochtones qui en sont à l’origine. Nous montrerons ensuite en quoi cette super-héroïne dont les pouvoirs apparaissent après qu’elle a été sexuellement agressée, tend à dénoncer et lutter contre les féminicides touchant les femmes autochtones. Enfin, nous nous demanderons comment cette bande dessinée pourrait laisser entrevoir l’émergence d’une super-héroïne autochtone éco-féministe.
Keywords: amérique du nord; amériques; approches et analyses; arts; bande-dessinée; cours; discipline; environnement; féminicide; féminisme autochtone; féminisme pop; histoire et politique; justice sociale; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; super-héroïnes; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Climate change, colonialism, and women’s well-being in Canada: What is to be done? - Williams, Lewis (Canadian Journal of Public Health, 2018)
The impacts of accelerating climate change across Canada are unequally distributed between populations and regions. Emerging evidence shows climate change and resultant policies to be worsening gendered social and economic inequities between women and men, with women’s participation largely absent in climate change research and decision-making. These dynamics are resulting in negative impacts for women’s well-being, with Indigenous and historically marginalized women at increased risk of experiencing health inequities as a result of climate change. To date, public health discourse has largely failed to incorporate gender as a key determinant of health in discussions of climate change impacts on populations. Paralleling this lack of development, the entangled relationship between climate and colonialism tends to be subsumed under the term “Aboriginality” within health determinants discourse. This commentary on gender and climate change in Canada is framed within a radical intersectional approach as an alternative course of public health analysis and action aimed at addressing resulting health and power inequities. Following an overview of evidence regarding the gendered impacts of climate change on women’s work, roles, agency, and well-being, several possible public health action areas on climate change and gender are highlighted as necessary components for resilient communities capable of meeting contemporary challenges.
Keywords: amériques; approches et analyses; canada; changements climatiques; environnement; intersectionnalité; invisibilisation des femmes autochtones; projet charge mentale; régions géographiques; santé; santé des femmes*; sexisme; système colonial; systèmes d'oppressions; thématiques

Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power--in the form of economic, social, symbolic, and cultural capital--is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis

Plan Nord - Où sont les femmes autochtones ? - Arnaud, Aurélie (Recherches amérindiennes au Québec, 2011)
Parmi les sujets absents du débat sur les impacts et les conséquences du Plan Nord se trouvent, invisibles, les femmes autochtones. Celles qui constituent plus de 50 % de la population autochtone dans le Nord sont les moins écoutées, les moins consultées, les plus vulnérables. La question est absente et il y a peu de données disponibles quant à l’impact des activités minières ou des chantiers hydroélectriques sur la condition des femmes. Or, l’expérience de Femmes autochtones du Québec révèle que ce type de développement a souvent des incidences négatives sur la situation des femmes autochtones dans les communautés en exacerbant les préjugés, les violences et les inégalités. Pour poser la réalité des femmes autochtones dans et hors réserve, il faut préciser qu’en 2001, les femmes autochtones enregistraient un taux de monoparentalité deux fois plus élevé que celui des femmes non autochtones (19 % contre 8 %). Les nombreuses familles dirigées par des femmes autochtones sont donc plus dépendantes de l’aide sociale que les hommes autochtones le sont.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; inégalités; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

L'association des femmes inuites du Nunavik Saturviit : porteuses d'espoir et de paix - Koperqualuk, Lisa Q. (2008)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; environnement; famille; féminisme autochtone; inégalités; maternité; nunavik; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; violences

« Des femmes et de la territorialité » Début d’un dialogue sur la nature sexuée des droits des autochtones - Woudenberg, Gerdine Van; Lapierre, Christine (Recherches amérindiennes au Québec, 2004)
Cet article, qui se situe dans l’ensemble des discours sur les droits des autochtones, explore de façon spécifique le sujet du rapport des femmes à la territorialité. En utilisant comme étude de cas les cultures wabanakies de la côte Est, l’auteure réexamine de manière critique les documents historiques pour analyser le rapport des femmes au « lieu » à travers leur relation à leur environnement et elle étudie comment le contexte de cette relation a été transformé par les processus de colonisation. Puisque ce texte s’insère dans le large champ des discours sur les droits autochtones, il soulève des questions importantes sur la position des femmes autochtones dans les processus actuels de reconnaissance des droits et des titres, non seulement comme participantes actuelles mais aussi comme acteurs historiques.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; environnement; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; territoire; thématiques; wabanakie

Policing the national body: Sex, race, and criminalization - Silliman, Jael Miriam; Bhattacharjee, Anannya; Davis, Angela Y.; Committee on Women, Population, and the Environment (South End Press, 2002)
Keywords: amériques; approches et analyses; corps; environnement; justice reproductive; maternité; nationalisme; racisme; régions géographiques; santé; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis